VOCATIONAL HIGH SCHOOL ENGLISH TEACHERS’ PERCEPTION TOWARDS THE ROLE OF PLATFORM MERDEKA MENGAJAR (PMM) IN IMPROVING THEIR TEACHING PERFORMANCE - Riny Anggraeni Ali; Nurdin Noni; Munir Munir; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Platform Merdeka Mengajar (PMM) has been introduced as an effort to improve teachers’ performance by providing access to various teaching resources and professional development programs. However, how vocational high school English teachers perceive the role of PMM in enhancing their teaching practices remains underexplored. This study aimed to investigate Vocational High School English teachers’ perceptions of PMM and its role in improving their teaching performance. A descriptive qualitative research design was employed, and data were collected through an interview to some of Vocational High School English teachers selected using a stratified sampling technique based on employment status, namely PNS (Civil servants), PPPK (Government employees), and Honorer (Non-permanent teachers). Descriptive analysis was conducted to examine teachers' responses. The findings revealed that most teachers perceive PMM positively, particularly in terms of providing accessible teaching materials, many useful features, and facilitating the teachers to communicate with many teachers across Indonesia. However, some teachers have negative perception about the platform with some reasons. This study highlights the need for improved the platform to maximize its benefits for vocational high school teachers.